Pelatihan Penggunaan Aplikasi Google Form, Puzzlemaker, dan Quizizz sebagai Media Evaluasi Pembelajaran bagi Guru SDI Waemata - Fransiska Atrik Halim (Jurnal Nasional Pengabdian Masyarakat, 2023)
One important part of the learning process is evaluation. Implementation of learning evaluation can be done with the help of technology, for example by carrying out computer-based tests. Teachers can also use applications such as Google Forms, Puzzlemaker, and Quizizz as learning evaluation media which are considered more effective and increase student activity. Teachers at Waemata elementary school still use the old way of carrying out learning evaluations by writing test questions on the board for students to complete. Some teachers already know that several applications that can be used to evaluate learning, but they don't know how to use them. Therefore, the solution offered is the implementation of training on using the Google Form, Puzzlemaker, and Quizizz applications which can be used as learning evaluation media. The methods used in this activity are lectures, discussions, and practice using the Google Form, Puzzlemaker, and Quizizz applications as learning evaluation media. As a result, teachers can understand and use these three applications to make a test.